BAHASA AKUNTANSI SEBAGAI âDISCOURSE-DRIVENâ DALAM BUDAYA KAPITALISME BARU - Witono, Banu (Universitas Muhammadiyah Surakarta, 2016)
It is undeniable that accounting as a science or practice developed at this time considered to be born of the